Disruptive Imports: The Impact Of The Chinese Rubber Imports On Employment In The South African Rubber Manufacturing Industry - Donal, Ryan; Chikandiwa, Christopher Tarisayi (Acta Universitatis Danubius. Œconomica, 2023)
The main objective of this article is to shed some light on one of the burning questions in the African region on the effect of imports on economy and employment. As such, the article analysed the effect of the Chinese imports on employment in the South African rubber manufacturing industry using secondary data. The modified Chenery model was applied for the analysis. The findings of this study provide tentative evidence that the import penetration had a negative linear effect on employment. The results illustrate that importation of the rubber products has had a negative effect on domestic employment over the past 15 years. The study recommends that the rubber manufacturing companies should focus on collaboration, which should lead to a more sustainable level of growth. This article is valuable as it does not only conceptualise the rubber manufacturing industry and reveal the effect of Chinese imports on the industry, but it also suggests some strategic collaboration as a way to build resilience and sustainable growth.